Improving Discipline Behavior through the Implementation of Reward and Punishment among Children Aged 4-5 Years - Andriani, Dessy; Effendi, Darwin; Maryani, Desy (Universitas Sebelas Maret, 2026)
This study is a Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted over two cycles involving 11 children aged 4–5 years.. The study aims to analyze the effectiveness of implementing reward and punishment methods in improving disciplinary behavior among children. Data were collected through observation using a disciplinary behavior assessment sheet based on TCP (Total Behavior Achievement) indicators—a total score representing the achievement of various established disciplinary behavior indicators. Initial observations during the Pre-Cycle stage showed low levels of disciplinary behavior, with an average TCP score of 18.5, placing the majority of children in the